Evaluation of the Global Entrepreneurship Index validity - Avancci Dionisio, Eduardo; Silva, Dirceu; Quadros Carvalho, Ruy; Inácio Júnior, Edmundo (REGEPE Entrepreneurship and Small Business Journal, 2022)
Purpose: our objective is to assess whether the Global Entrepreneurship Index (GEI) is a valid methodology for measuring the national systems of entrepreneurship. Theoretical framework: we use the structural equation modeling (SEM) as a theoretical lens to evaluate the Global Entrepreneurship Index. Design/methodology/approach: to achieve the research objective, we perform structural equation modeling to measure the formative model of GEI, using the SmartPLS 3.0 software, in order to verify the convergent validity of the constructs; the collinearity of indicators and their relevance for measuring entrepreneurship. Findings: the results obtained show that the sub-indices and indicators are adequate to measure entrepreneurship. However, we identified that there is a need to replace the micro-level components of the opportunity perception and networking indicators which provide distorted results of what is understood as productive or high impact entrepreneurship. Research, practical and social implications: the main contributions of our study are directed to the indicators’ developers. We suggest the use of components that capture aspects associated with high-impact or technology-based entrepreneurship instead of any attempt to create a new business, as our results indicate that generic components provide short-sighted results on the state of entrepreneurship, hampering comparative studies at the country-level. Originality/value: although the GEI is based on the OECD recommendations for the construction of composite indicators (indices), we have not identified any studies (not even performed by the GEI developers) on the validity of the index as a methodology for measuring entrepreneurship.